Implementation of Teaching Materials Containing Majalengka Local Wisdom to Improve Ecoliteracy in Elementary Schools - Devi Afriyuni Yonanda; Dudu Suhandi Saputra; Irma Sofiasyari; Islahuddin Islahuddin; Devita Cahyani Nugraheny (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThe environment is a precious resource that requires maintenance and preservation. Nonetheless, awareness regarding the significance of environmental conservation requires enhancement, particularly among elementary school students. This quasi-experimental research aimed to enhance the eco-literacy of elementary school students. This study's subjects were purposively selected elementary school students from Majalengka Regency. The research data consisted of both test and non-test instruments. Subsequent to data collection, it was analyzed utilizing a qualitative method with inductive techniques and a quantitative method employing statistical tests. The findings indicated a substantial enhancement in eco-literacy among the experimental group relative to the control group. The results demonstrate that utilizing teaching materials grounded in local wisdom can effectively enhance elementary students' comprehension and awareness of environmental issues. This study significantly contributes to the advancement of environmental education in Indonesia by highlighting the necessity of incorporating and integrating local values into eco-literacy instruction in elementary schools.Keywords: teaching materials, local wisdom, ecoliteracy.AbstrakLingkungan merupakan sumber daya yang sangat berharga yang perlu dipelihara dan dilestarikan. Meskipun demikian, kesadaran akan pentingnya pelestarian lingkungan perlu ditingkatkan, khususnya di kalangan siswa sekolah dasar. Penelitian kuasi-eksperimental ini bertujuan untuk meningkatkan literasi ekologi siswa sekolah dasar. Subjek penelitian ini adalah siswa sekolah dasar yang dipilih secara purposif di Kabupaten Majalengka. Data penelitian terdiri dari instrumen tes dan non-tes. Setelah data terkumpul, data dianalisis menggunakan metode kualitatif dengan teknik induktif dan metode kuantitatif dengan menggunakan uji statistik. Temuan penelitian menunjukkan peningkatan yang substansial dalam literasi ekologi di antara kelompok eksperimen dibandingkan dengan kelompok kontrol. Hasil penelitian menunjukkan bahwa penggunaan bahan ajar yang didasarkan pada kearifan lokal dapat secara efektif meningkatkan pemahaman dan kesadaran siswa sekolah dasar tentang isu-isu lingkungan. Penelitian ini memberikan kontribusi yang signifikan terhadap kemajuan pendidikan lingkungan di Indonesia dengan menyoroti perlunya menggabungkan dan mengintegrasikan nilai-nilai lokal ke dalam pengajaran literasi ekologi di sekolah dasar.Kata kunci: bahan ajar, kearifan lokal, literasi ekologi.